2017
DOI: 10.1371/journal.pone.0182294
|View full text |Cite
|
Sign up to set email alerts
|

The frontline of immune response in peripheral blood

Abstract: Peripheral blood is an attractive source for the discovery of disease biomarkers. Gene expression profiling of whole blood or its components has been widely conducted for various diseases. However, due to population heterogeneity and the dynamic nature of gene expression, certain biomarkers discovered from blood transcriptome studies could not be replicated in independent studies. In the meantime, it’s also important to know whether a reliable biomarker is shared by several diseases or specific to certain heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Thus, the transcript isoform repertoire of CD8 + ptPBLs is much larger than that of CD8 + TIL, likely due to similarities for tissue infiltrates but with a few notable dif-identifying pan-pathology genes. We thus compared our pan-cancer DEGs to data sets from another study aimed at identifying frontline biomarkers common to numerous pathologies (30). Strikingly, 82.1% of our ptPBL-based and 42.8% of our TIL-based top 200 pan-cancer FIR-DEGs were confirmed by their findings, with 51% of 467 pan-cancer DEGs and 59% of the top 100 pan-cancer DEGs present ( Figure 6F).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Thus, the transcript isoform repertoire of CD8 + ptPBLs is much larger than that of CD8 + TIL, likely due to similarities for tissue infiltrates but with a few notable dif-identifying pan-pathology genes. We thus compared our pan-cancer DEGs to data sets from another study aimed at identifying frontline biomarkers common to numerous pathologies (30). Strikingly, 82.1% of our ptPBL-based and 42.8% of our TIL-based top 200 pan-cancer FIR-DEGs were confirmed by their findings, with 51% of 467 pan-cancer DEGs and 59% of the top 100 pan-cancer DEGs present ( Figure 6F).…”
Section: Resultsmentioning
confidence: 66%
“…Transcriptomic data sets from patients with melanoma and non-small-cell lung cancer (NSCLC) treated with anti-PD-1 therapy are available from Hugo et al (31) and Rizvi et al (32). The HIV-1 elite controllers data set is available from Zhang et al (29), and the bacterial data sets are listed in Song et al (30). Comprehensive pathway enrichment analysis and PPI analyses are available as Supplemental Data.…”
mentioning
confidence: 99%
“…Mean age tended to be older in MMD patients than in healthy controls (34.61 ± 14.81 vs 44.35 ± 8.42, p = 0.01) from the qRT-PCR group. However, our previous study has shown that effect of age on gene expression in peripheral blood was so weak that expression of only six genes including NELL2 , CCR2 , CCR7 , MYC , LTB and FAM102A displayed weak negative correlation (Pearson correlation coefficients varying from -0.29 to -0.47) with age in four public datasets[48]. Baseline characteristics of all participants were shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In the past decade, host transcriptional response has emerged as a promising alternative for identifying infection (Ahn et al, 2013;Heinonen et al, 2016;Kaforou et al, 2013;Pankla et al, 2009;Zhai et al, 2015). A consistent signature for respiratory viral infection has been reported, a group of interferon-stimulated genes (ISGs) (Liu et al, 2016;Song et al, 2017;Zaas et al, 2013;Zhai et al, 2015). Several studies have attempted to distinguish bacterial infection from viral or other sources of infection.…”
Section: Introductionmentioning
confidence: 99%